LI-RADS Treatment Response Algorithm: Performance and Diagnostic Accuracy With Radiologic-Pathologic Explant Correlation in Patients With SBRT-Treated Hepatocellular Carcinoma - Mendiratta-Lala, Mishal; Aslam, Anum; Maturen, Katherine E; Westerhoff, Maria; Maurino, Chris; Parikh, Neehar D; Sun, Yilun; Sonnenday, Christopher J; Stein, Erica B; Shampain, Kimberly L; Kaza, Ravi K; Cuneo, Kyle; et al. (International journal of radiation oncology, biology, physics, 2022)
Our purpose was to evaluate the accuracy of LI-RADS Treatment Response Algorithm (LR-TRA) for assessing the viability of hepatocellular carcinoma (HCC) treated with stereotactic body radiation therapy (SBRT), using explant pathology as the gold standard. This retrospective study included patients who underwent SBRT for locoregional treatment of HCC between 2008 and 2019 with subsequent liver transplantation. Five radiologists independently assessed all treated lesions by using the LR-TRA. Imaging and posttransplant histopathology were compared. Lesions were categorized as either completely (100%) or incompletely (<100%) necrotic, and performance characteristics and predictive values for the LR-TR viable and nonviable categories were calculated for each reader. Interreader reliability was calculated using the Fleiss kappa test. A total of 40 treated lesions in 26 patients (median age, 63 years [interquartile range, 59.4-65.5]; 23 men) were included. For lesions treated with SBRT, sensitivity for incomplete tumor necrosis across readers ranged between 71% and 86%, specificity between 85% and 96%, and positive predictive value between 86% and 92%, when the LR-TR equivocal category was treated as nonviable, accounting for subject clustering. When the LR-TR equivocal category was treated as viable, sensitivity of complete tumor necrosis for lesions treated with SBRT ranged from 88% to 96%, specificity from 71% to 93%, and negative predictive value from 85% to 96%. Interreader reliability was fair (k = 0.22; 95% confidence interval, 0.13-0.33). Although a loss of arterial phase hyperenhancement (APHE) was highly correlated with pathologically nonviable tumor on explant, almost half of the patients with APHE had pathologically nonviable tumor on explant. LR-TRA v2018 performs well for predicting complete and incomplete necrosis in HCC treated with SBRT. In contrast to other locoregional therapies, the presence of APHE after SBRT does not always indicate viable tumor and suggests that observation may be an appropriate strategy for these patients.